WORK-LIFE BALANCE, KOMITMEN ORGANISASIONAL, DAN KEPUASAN KERJA KARYAWAN MILENIAL - Nico Kosasih (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the effect of work-life balance (WLB) on job satisfaction, with organizational commitment as a mediating variable among millennials in the creative industry. The research employs a quantitative approach with an explanatory design. The sample consists of 120 respondents who are millennial employees in the creative industry sector in Banjarmasin City, selected using purposive sampling. Data analysis was conducted using Partial Least Squares (SmartPLS 2.5) to examine both direct and indirect relationships among variables. The results show that work-life balance has a positive and significant effect on organizational commitment and job satisfaction. Organizational commitment also has a positive effect on job satisfaction and partially mediates the relationship between WLB and job satisfaction. The R² values of 0.561 for organizational commitment and 0.684 for job satisfaction indicate strong predictive power of the model. These findings confirm that work-life balance not only has a direct impact on job satisfaction but also enhances affective commitment, which strengthens employees’ emotional attachment to the organization. Practically, this study emphasizes the importance of social and managerial support, the implementation of flexible work policies, and psychological empowerment to improve the well-being and retention of millennial employees in the creative sector.